2018
DOI: 10.3390/soilsystems2040058
|View full text |Cite
|
Sign up to set email alerts
|

Products of Hexavalent Chromium Reduction by Green Rust Sodium Sulfate and Associated Reaction Mechanisms

Abstract: The efficacy of in vitro Cr(VI) reduction by green rust sulfate suggests that this mineral is potentially useful for remediation of Cr-contaminated groundwater. Previous investigations studied this reaction but did not sufficiently characterize the intermediates and end products at chromate (CrO42−) concentrations typical of contaminant plumes, hindering identification of the dominant reaction mechanisms under these conditions. In this study, batch reactions at varying chromate concentrations and suspension de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 61 publications
4
19
1
Order By: Relevance
“…GR phases can be easily engineered for a wide-range of applications such as catalysis, electrochemistry, and environmental remediation (Bhave and Shejwalkar, 2018;Chen et al, 2018;Huang et al, 2019;Zhang et al, 2018). In particular, they are promising reactants for ground water remediation where they have been shown to remove toxic metal contaminants from water by adsorption (Jönsson and Sherman, 2008;Mitsunobu et al, 2009;Perez et al, 2019), reduction (O'Loughlin et al, 2003;Skovbjerg et al, 2006;Thomas et al, 2018), interlayer intercalation (Refait et al, 2000) and substitution of structural Fe (Ahmed et al, 2008;Refait et al, 1990 Christiansen et al). The structural Fe(II)/Fe(III) ratio of 2 has been determined by Mössbauer spectroscopy, chemical analysis, and X-ray diffraction (Christiansen et al, 2009;Génin et al, 1996;Hansen et al, 1994;Perez et al, 2019;Refait et al, 1999Refait et al, , 1990.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…GR phases can be easily engineered for a wide-range of applications such as catalysis, electrochemistry, and environmental remediation (Bhave and Shejwalkar, 2018;Chen et al, 2018;Huang et al, 2019;Zhang et al, 2018). In particular, they are promising reactants for ground water remediation where they have been shown to remove toxic metal contaminants from water by adsorption (Jönsson and Sherman, 2008;Mitsunobu et al, 2009;Perez et al, 2019), reduction (O'Loughlin et al, 2003;Skovbjerg et al, 2006;Thomas et al, 2018), interlayer intercalation (Refait et al, 2000) and substitution of structural Fe (Ahmed et al, 2008;Refait et al, 1990 Christiansen et al). The structural Fe(II)/Fe(III) ratio of 2 has been determined by Mössbauer spectroscopy, chemical analysis, and X-ray diffraction (Christiansen et al, 2009;Génin et al, 1996;Hansen et al, 1994;Perez et al, 2019;Refait et al, 1999Refait et al, , 1990.…”
Section: Introductionmentioning
confidence: 99%
“…Cr, Se, U) or its adsorption uptake (e.g. As) (Jönsson and Sherman, 2008;O'Loughlin et al, 2003;Perez et al, 201λ;Skovbjerg et al, 2006;Thomas et al, 2018). One way to check the stability of GR over time is to monitor the Fe(II)/Fe(III) ratio following interaction with metals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Green rust 1 has a narrow interlayer spacing of ~ 8 Å occupied by chloride or carbonate, while green rust 2 has a broad interlayer spacing (~ 11 Å) typically occupied by sulfate, which allows exchange of tetrahedral oxyanions and subsequently reduction and sequestration of these substances in the reaction product's interlayer [13][14][15]. Therefore, it is a promising reagent for exchange and/or reduction of selected groundwater contaminants such as As [16,17], NO 3[18,19], U (VI) [15,20], Se (VI) [21,22], Np [23] and Cr(VI) [13,14,[24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Bond and Fendorf [13] and Skovbjerg et al [14] concluded that these products formed due to exchange of chromate for interlayer sulfate followed by reduction. More recently, our previous study [28] reacted green rust with a series of initial chromium concentrations typical of contaminant plumes and determined that the speciation of chromium in the reaction product is correlated to the initial concentration. Although more goethite was found in the reaction products formed at higher initial concentrations, Cr(III) hydroxide, presumably located on the oxidized green rust particle surfaces, was the primary Cr(III) carrier phase produced.…”
Section: Introductionmentioning
confidence: 99%